Evaluation of liraglutide in the treatment of Alzheimer's disease. (31st December 2021) - Edison, Paul; Femminella, Grazia Daniela; Ritchie, Craig W.; Holmes, Clive; Walker, Zuzana; Ridha, Basil H; Raza, Sanara; Livingston, Nicholas R; Nowell, Joseph; Busza, Gail; Frangou, Eleni; Love, Sharon; et al.
Abstract: Background: Liraglutide is a glucagon‐like peptide‐1 (GLP‐1) analogue licensed for the treatment of type 2 diabetes. Preclinical evidence in transgenic models of Alzheimer's disease suggests that liraglutide exerts neuroprotective effects by reducing amyloid oligomers, normalising synaptic plasticity and cerebral glucose uptake, and increasing the proliferation of neuronal progenitor cells. Methods: ELAD is a 12‐month, multi‐centre, randomised, double‐blind, placebo‐controlled, phase IIb trial of liraglutide in participants with mild to moderate Alzheimer's dementia, conducted at several centres in the UK – (NCT01843075). [18F]FDG‐PET and MRI brain scans of all patients will be performed at baseline and after 12 months treatment with liraglutide or matching placebo. Once enrolled, all subjects had a neuropsychological battery of tests All scans and tests will be repeated after 12 months. A total of 204 participants were randomised to receive either liraglutide or placebo as a daily subcutaneous injection for 12 months. The primary objective was to evaluate the change in cerebral glucose metabolic rate in the cortical regions (hippocampus, medial temporal lobe, and posterior cingulate) from baseline to 12‐month follow‐up in participants with Alzheimer's disease receiving treatment with liraglutide compared to those receiving placebo. The key secondary outcomes were the change from baseline to 12 months in z scores for clinical and cognitive measures (Alzheimer's Disease Assessment Scale – Cognitive Subscale and Executive domain scores of the Neuropsychological Test Battery, Clinical Dementia Rating Sum of Boxes, and Alzheimer's Disease Cooperative Study – Activities of Daily Living) and the incidence and severity of treatment‐emergent adverse events or clinically important changes in safety assessments. Other secondary outcomes were 12‐month change in magnetic resonance imaging volume, diffusion tensor imaging parameters, and changes in composite scores using support machine vector analysis in the treatment group compared with the placebo group. Results: The study demonstrated that liraglutide treated patients performed significantly better than placebo arm in temporal lobe and whole cortical MRI volume and cognitive function measured by ADAS‐EXEC (ADAS‐Cog with Executive domains of the Neuropsychological Test Battery). Conclusion: This demonstrates that GLP1 analogues can improve cognitive function and MRI volume in AD subjects and could be a potential treatment for treatment for Alzheimer's